Answer:
The value of f(x) - g(x) is:
f(x) - g(x) = 2x² + 6x - 4
Step-by-step explanation:
Given
f(x) = 3x² + x - 3
g(x) = x² - 5x + 1
To determine
f(x) - g(x)
Using the formula
f(x) - g(x) = 3x² + x - 3 - ( x² - 5x + 1)
= 3x² + x - 3 - x² + 5x - 1
= 2x² + 6x - 4
Therefore, the value of f(x) - g(x) is:
f(x) - g(x) = 2x² + 6x - 4
Answer:
You need to have both the opposite and adjacent side of the right angled triangle. Tan = Opp/Adj
Step-by-step explanation:
Tangents are pretty much everywhere. A good example is maybe a slide at the playground. You’d need the tangent to figure out the angle of the slide and how it is.
The radius from the center of a circle to the point of tangency point shows that it would be perpendicular to the tangent line considering that anything with a radius is circular and the tangent line is… a line, making it impossible to be parallel.
Answer:
35/4 minutes per mile
Step-by-step explanation:
rate = time/distance, therefore the answer is 35/4
Your line is wrong from the start. But for the equation: